POPULATION DYNAMICS OF SILVERBELLY LEIOGNATHUS JON ESI IN PALK BAY - Venkataraman, G; Badrudeen, M; Thiagarajan, R (Indian Journal of Fisheries, 2011)
Based on catoh, effort and length-distribution data on Leiognathus jonesi collectedat Mandapam over a period of sk seasons, age and growth, selection factor,coefficient of total mortality (Z) and coefficient of natural mortality (M) werederived1. For the estimated' natural mortality rclte (2.1) and for the mesh size(25 mm codend) now in operation, the optimum effort has been found to bs50,000 standard night effort, (= 5,000 std. day effort), the yield per hundred recruitsbeing 310 g. The isopleth diagram indicates that there was overfishing ofsilverbellies in 1973-74 and 1974-75 when the effort far exceeded the optimum level.The isopleth diagram also shows that the present mesh size yields the best catchand an increase in mesh size to 35 mm or decrease to 15 mm leads only to adecrease in yield. For a scientific rwanagetnemt of the fishery, it is suggested thatthe effort be maintained at 50,0000 night standard effort with the present meshsize at 25 mm so as to obtain sustained yield of this fish in the coming years.